The interpersonal benefits of goal adjustment capacities: the sample case of coping with poor sleep in couples - Barlow, Meaghan A.; Wrosch, Carsten; Hoppmann, Christiane A. (Frontiers in Psychology, 2024)
Introduction This study examined the role of goal adjustment capacities and coping in the association between spousal sleep efficiency and relationship satisfaction in romantic couples. Method A community lifespan sample of 113 heterosexual couples (age range = 21–82 years) was recruited using newspaper advertisements in the Greater Montreal Area from June 2011 to December 2012. Participants completed study measures (i.e., Goal Adjustment Scale, Brief Pittsburgh Sleep Quality Index, Relationship Assessment Scale, and the Brief Cope) at two time points, ~1 year apart. Results The results of actor-partner interdependence models with moderation (MIXED procedure in SPSS) reveal that goal disengagement buffered people from worsening relationship satisfaction associated with poor spousal sleep [95% CI B (−1.17, −0.12)], in part via increases in actor active coping [95% CI B (−0.32, −0.02)] and decreases in partner self-blame [95% CI B (−0.28, −0.01)]. Goal reengagement was related to diminished relationship satisfaction in response to poor own sleep [95% CI B (0.59, 1.79)], in part through increases in actor behavioral disengagement [95% CI B (0.05, 0.41)]. Discussion These findings point to a need for future studies to examine goal adjustment capacities and relationship-specific coping strategies as potential targets of intervention to maintain peoples' relationship satisfaction in the face of sleep problems.